The Effect Of Leadership, Work Environment, And Training On The Performance Of Teachers And Administrative Staff At Smkn 2 Kota Bengkulu - Silvia Ulandari; Ida Anggriani; Ramadhan Subhi (Journal of Business Management, 2026)
Human resources are an important factor in determining the success of an organization, including educational institutions. Improvements in the quality of human resources can be reflected in the optimal performance of teachers and staff. This study aims to analyze the influence of principal leadership, work environment, and training on the performance of teachers and administrative staff at SMKN 2 Bengkulu City. This study used a quantitative approach with a population of 148 people and a sample of 74 respondents through accidental sampling. Data collection was conducted through questionnaires and analyzed using validity and reliability tests, multiple linear regression, the coefficient of determination, and hypothesis testing using SPSS version 25. The results show that leadership (X1), work environment (X2), and training (X3) have a significant and positive effect on the performance of teachers and staff at SMK Negeri 2 Kota Bengkulu (Y). Partially, leadership has a significant effect with a t-value (2.445) > t-table (1.653) and a significance value of 0.001 < 0.05. The work environment also has a significant effect with a t-value (2.589) > t-table (1.667) and a significance value of 0.003 < 0.05. Training has the strongest effect with a t-value (3.763) > t-table (1.667) and a significance value of 0.002 < 0.05. Simultaneously, the three independent variables (leadership, work environment, and training) had a significant effect on the performance of teachers and staff with a t-value (7.894) > t-table (2.73) and a significance level of 0.03 < 0.05. The coefficient of determination (R²) value of 0.781 indicates that 78.1% of the variation in teacher and staff performance is influenced by these three variables, while the remaining 21.9% is influenced by other factors outside this study. The regression equation obtained is:Y = 31.901 + 0.579X₁ + 0.296X₂ + 0.153X₃ + 8.768,which shows that any increase in leadership, work environment, and training will positively improve teacher and staff performance.